표토복원지 재녹화를 위한 식물생장촉진 미생물 선별 및 활성 검사 - 김지슬(Ji Seul Kim); 김준호(Jun Ho Kim); 이은영(Eun Young Lee) (Daehan hwan'gyeong gonghag hoeji, 2021)
목적:본 연구는 훼손된 표토의 재식생화를 통한 복원 중 식물생장촉진미생물의 적용 가능성을 알아보기 위하여 수행되었다. 방법:현장 복원지에 적용할 식생으로 병꽃나무, 조팝나무, 소나무 및 슈크령을 선정하였다. 국내 공원부지 및 등산 산책로 등에 서식하는 동일한 종의 식물 근권으로부터 식물생장촉진미생물의 분리를 시도하였다. 인산가용화능, siderophore 생성능, IAA생성능, ACC deaminase 활성능 등의 식물생장촉진 활성을 검사하여 최종 적용할 종을 선정한 후 동정하였다. 식물생장촉진활성이 확인된 균주 중 Arthrobacter sp. 와 Paraburkholderia terrae를 각각 병꽃나무와 소나무에 적용하여 활성을 확인하기 위한 pot 실험을 진행하였다. 결과 및 토의:병꽃나무, 조팝나무, 소나무, 및 슈크령으로부터 45개의 균주를 분리하였고, 인산가용화능과 siderophore 생성능이 확인된 16개의 균주를 대상으로 IAA생성능, ACC deaminase 활성능을 확인하였다. 식물생장촉진능이 우수한 균주를 선정 후 동정하여 Cupriavidus sp, Arthrobacter sp., Pseudomonas fluorescens, Pseudomonas sp., Paraburkholderia terrae등의 균주를 확보하였다. 이 중 Arthrobacter sp. 1B2와 Paraburkholderia terrae 1P2 균주를 각각 병꽃나무와 소나무에 적용하여 식물생장이 촉진됨을 확인하였다. 결론:식물생장촉진미생물을 이용한 생물검정 실험 및 현장적용은 주로 초본류(벼과, 옥수수, 귀리 등)를 대상으로 연구되어왔다. 그러나 본 연구에서는 환경이 열악하고 유기물과 무기물의 함량이 부족한 심토 함량이 높은 훼손지를 대상으로 적용 대상 식물이 관목류로서 길이 생장이 현저하게 진행되지 않는 식물이다. 따라서, 인산가용화 활성 및 siderophore능과 같이 무기물의 흡수에 초점을 둔 식물생장촉진미생물의 활성에 알아보고 생물검정을 수행하여 활성을 확인한 점에서 의의가 있다. Objectives:This study was conducted to investigate the applicability of plant growth promoting microorganisms during restoration through re-vegetation of damaged topsoil. Methods:As the vegetation to be applied to the restoration site, Weigela subsessilis, Spiraea prunifolia, Pine densiflora, Pennisetum alopecuroides were selected. An attempt was made to isolate plant growth promoting microorganisms from the root zone of plants of the same species inhabiting domestic park sites and hiking trails. Plant growth promoting activities such as phosphate solubilization ability, siderophore production ability, IAA production ability, and ACC deaminase production ability were examined, and the species to be finally applied was selected and then identified. Among the strains whose plant growth promoting activity was confirmed, Arthrobacter sp. 1B2 and Paraburkholderia terrae 1P2 were applied to the genitalia and pine, respectively, and a pot experiment was conducted to confirm the activity. Results and Discussion:Forty-five strains were isolated from Weigela subsessilis, Spiraea prunifolia, Pine densiflora, Pennisetum alopecuroides and the IAA-producing ability and ACC deaminase-producing ability were confirmed for 16 strains whose phosphate solubilizing ability and siderophore-producing ability were confirmed. After selecting and identifying strains with excellent plant growth promoting ability, strains such as Cupriavidus sp, Arthrobacter sp., Pseudomonas fluorescens, Pseudomonas sp., Paraburkholderia terrae were obtained. Among them, Arthrobacter sp. 1B2 and Paraburkholderia terrae 1P2 strains were applied to genitalia and pine, respectively, and it was confirmed that plant growth was promoted. Conclusions:Bioassay experiments and field applications using plant growth promoting microorganisms have been mainly studied for herbaceous species (Grandaceae, corn, oats, etc.). However, in this study, the applied plants are shrubs class, which do not significantly grow in length, targeting damaged areas with high subsoil content, which are poor in environment and insufficient in organic and inorganic matter. Therefore, it is meaningful in that the activity of plant growth promoting microorganisms focused on absorption of inorganic substances, such as phosphate solubilization activity and siderophore ability, was investigated and the activity was confirmed by performing a bioassay. KCI Citation Count: 0